Chemical analysis of amyloid β aggregation inhibitors derived from Geranium thunbergii. (15th August 2022) - Kubo, Kenji; Watanabe, Hikaru; Kumeta, Hiroyuki; Aizawa, Tomoyasu; Seki, Chigusa; Nakano, Hiroto; Tokuraku, Kiyotaka; Uwai, Koji
Graphical abstract: Highlights: Geraniin (1 ) isolated from Geranium thunbergii inhibited amyloid beta aggregation. Geraniin was hydrolyzed under assay conditions to yield active derivatives. Hydrolyzed compounds gallic acid (2 ) and corilagin (5 ) inhibited amyloid aggregation. Interaction between corilagin (5 ) andh Aβ was confirmed using STD-NMR. G. thunbergia, geraniin (1 ), gallic acid (2 ) and corilagin (5 ) might be useful for AD prevention. Abstract: Amyloid β (Aβ) aggregates in the brains of patients with Alzheimer's disease (AD) and accumulates via oligomerization and subsequent fiber elongation processes. These toxicity-induced neuronal damage and shedding processes advance AD progression. Therefore, Aβ aggregation-inhibiting substances may contribute to the prevention and treatment of AD. We screened for Aβ42 aggregation inhibitory activity using various plant extracts and compounds, and found high activity for a Geranium thunbergii extract (EC50  = 18 μg/mL). Therefore, we screened for Aβ42 aggregation inhibitors among components of a G. thunbergii extract and investigated their chemical properties in this study. An active substance was isolated from the ethanol extract of G. thunbergii based on the Aβ42 aggregation inhibitory activity as an index, and the compound was identified as geraniin (1 ) based on spectral data. However, although geraniin showed in vitro aggregation-inhibition activity, no binding to Aβ42 was observed via saturation transfer difference-nuclear magnetic resonance (STD-NMR). In contrast, the hydrolysates gallic acid (2 ) and corilagin (5 ) showed aggregation-inhibiting activity and binding was observed via STD-NMR. Therefore, the hydrolysates produced under the conditions of the activity test may contribute to the Aβ42 aggregation-inhibition activity of G. thunbergii extracts. Geraniin derivatives may help prevent and treat AD.